2020
DOI: 10.1002/jmcd.12195
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Latinx Cultural Wealth to Create a College‐Going Culture in High School

Abstract: Capitalizing on Latinx students' aspirational, linguistic, social, navigational, familial, resistant, perseverant, and spiritual community cultural wealth (CCW) can help school counselors empower Latinx students. We outline and integrate critical race theory and CCW and demonstrate how communities of color bring assets and protective factors with them to their educational settings. We also examine how school counselors can utilize these eight forms of CCW to promote postsecondary opportunities for Latinx youth. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…Previous research (Vela-Gude et al, 2009) indicated that in schools with many Hispanic and Black students, schools or school counseling departments/programs devoted less time to college and career readiness. These schools often have fewer counselors and higher caseloads (Martinez et al, 2020; Nikischer et al, 2016; Vela et al, 2013). Indeed, research indicates that Hispanic and Black students rely more on school counselors for college-going information/counseling because they have less access or exposure to college information resources (Bryan et al, 2011; Vela et al, 2013, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research (Vela-Gude et al, 2009) indicated that in schools with many Hispanic and Black students, schools or school counseling departments/programs devoted less time to college and career readiness. These schools often have fewer counselors and higher caseloads (Martinez et al, 2020; Nikischer et al, 2016; Vela et al, 2013). Indeed, research indicates that Hispanic and Black students rely more on school counselors for college-going information/counseling because they have less access or exposure to college information resources (Bryan et al, 2011; Vela et al, 2013, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As former English teachers and curriculum developers for pre-college initiatives, we felt honored to support students' pathways to college, including first-generation students and students of color. It was often through the collective power among themselves, their families, community members and schools that they actualized their college dreams (Brooms and Davis, 2017;Holland, 2017;Martinez et al, 2020).While we find joy in remembering many success stories of students entering and graduating from college despite many odds, we also recognize the tremendous number of students who lacked and continue to lack access to both in and beyond school college-going support. While all stakeholders possess power and possibility in supporting students' college journeys, we focused on the tremendous potential teachers possess.…”
mentioning
confidence: 87%
“…As former English teachers and curriculum developers for pre-college initiatives, we felt honored to support students’ pathways to college, including first-generation students and students of color. It was often through the collective power among themselves, their families, community members and schools that they actualized their college dreams (Brooms and Davis, 2017; Holland, 2017; Martinez et al , 2020).…”
mentioning
confidence: 99%
“…By formatting the structure and content of the learning community based on Latinx culture, this program successfully increased the retention rate of nontraditional, working, commuter Latinx students in the teacher training project. R. R. Martinez et al (2020) suggested utilizing the Latinx community cultural wealth model (CCW; Yosso, 2005) composed of aspirational, linguistics, social, familial, resistant, perseverant, and spiritual capitals to create a college-going culture in high school. Further, they examined how the CCW can be used to promote postsecondary opportunities for Latinx youth.…”
Section: Enhancing Latinxs' Academic Successmentioning
confidence: 99%